A packaging film for solar modules and preparation method thereof

By using a crosslinking-type silane coupling agent in the photovoltaic adhesive film, a stable crosslinking network structure is formed, which solves the problem of poor adhesion with glass after aging of the photovoltaic adhesive film, and achieves high peel strength and long service life.

CN118755403BActive Publication Date: 2025-02-28ZHEJIANG XIANGBANG YONGSHENG NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411252227.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2025-02-28
Estimated Expiration
2044-09-09

AI Technical Summary

Technical Problem

The existing photovoltaic adhesive strength with the glass after aging is poor, which is prone to delamination failure.

Method used

A crosslinking type silane coupling agent is used, which contains two allyl groups, three siloxane bonds and one isocyanurate as a framework. Through crosslinking reaction with the matrix resin and chemical bonding with the glass, a stable crosslinking network structure is formed, which improves the body strength and adhesive properties of the adhesive film.

Benefits of technology

It achieves a high peel strength with the glass after PCT aging test, extends the service life of the photovoltaic module, and remains stable in high temperature and high humidity environments to avoid delamination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of encapsulation film, discloses a kind of encapsulation film for solar module and preparation method thereof, by mass fraction, the raw material of the encapsulation film comprises the following components: 100 parts of base resin, 0.1-1 parts of initiator, 0.5-1 parts of cross-linking silane coupling agent, 0.1-0.5 parts of cross-linking agent, 0.1-1 parts of anti-aging auxiliary agent; the cross-linking agent is at least one of cyanate and acrylate containing three or more carbon-carbon double bonds; the cross-linking silane coupling agent has a structure as shown in formula (I). The present invention adopts a cross-linking silane coupling agent of a specific structure, cooperates with the cross-linking agent component, increases the strength of the film body, and greatly improves the bonding strength with glass, and the stability under the environment of high temperature and high humidity is also higher, ensuring that long-term aging does not delaminate, and prolongs the life of the encapsulation film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of packaging adhesive films, and in particular to a packaging adhesive film for a solar module and a preparation method thereof. Background Art

[0002] Photovoltaic cells are very fragile as the core components of power generation and need to be protected by encapsulation films. Solar panels mainly use encapsulation films to bond cells, glass and back panels together, so that they are not affected by external forces during long-term outdoor operation and extend their service life. The rapid iteration of new battery technology has put forward more stringent requirements on the performance of encapsulation films, especially for single-glass encapsulation films.

[0003] At present, the main materials of adhesive film are EVA (ethylene-vinyl acetate copolymer) and POE (ethylene-alpha olefin copolymer). Both materials are polymer materials with low cohesive strength and low polarity. In particular, POE is a non-polar material. Therefore, a cross-linking agent must be added for curing to improve the body strength of the adhesive film. A coupling agent is also indispensable to increase the bonding performance with glass. This is because after wet heat aging, water vapor will diffuse on the interface between the adhesive film and the glass, and the adhesive film will absorb water and swell, resulting in a weakening of the peel strength between the adhesive film and the glass at the interface or even delamination. In order to ensure the good use effect of the adhesive film, it is necessary to improve its bonding performance, especially the bonding performance after aging.

[0004] The invention patent with publication number CN 112812695 B discloses a packaging film and its preparation method and application, wherein a base resin, a crosslinking agent, a co-crosslinking agent, a silane coupling agent and a light stabilizer, as well as optional fillers, photoinitiators, silane coupling agents, ultraviolet light absorbers and anti-PID additives are mixed and extruded to obtain the packaging film, wherein the co-crosslinking agent comprises a combination of an isocyanate co-crosslinking agent and an acrylate co-crosslinking agent. However, a large amount of auxiliary agent components are added to the packaging film, and the bonding performance during the use of the film and the lamination of the components will be affected, and the crosslinking degree of the packaging film is not significantly improved by only adding a co-crosslinking agent, so its bonding performance after aging is not greatly improved. Summary of the invention

[0005] In order to solve the problem in the prior art that photovoltaic films have poor adhesion to glass after aging and are prone to delamination failure, the present invention provides a packaging film for solar modules and a preparation method thereof. The packaging film has good bonding properties, especially maintains high peel strength with glass after PCT aging test, and can protect solar cells for long-term normal use outdoors.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] In the first aspect, the present invention provides a packaging film for solar modules, wherein the raw materials thereof include the following components by weight: 100 parts of base resin, 0.1-1 parts of initiator, 0.5-1 parts of cross-linking auxiliary silane coupling agent, 0.1-0.5 parts of cross-linking auxiliary agent, and 0.1-1 parts of anti-aging auxiliary agent; the cross-linking auxiliary agent is at least one of cyanate ester and acrylate containing three or more carbon-carbon double bonds; the cross-linking auxiliary silane coupling agent has a structure shown in the following formula (I):

[0008] (I); In formula (I), R1 is a C1-C5 alkyl group.

[0009] The present invention introduces a bifunctional silane coupling agent into the adhesive film, and the coupling agent contains two active allyl groups, three siloxane bonds, and an isocyanurate as a skeleton. Among them, the two allyl bonds can play the role of auxiliary cross-linking agents, the siloxane bond is a typical viscosity-enhancing functional group, and the isocyanurate is a very stable skeleton structure with excellent thermal stability and weather resistance. Specifically, the two allyl bonds are bonded to the matrix resin under the action of the initiator to form a three-dimensional cross-linked network structure. The isocyanurate skeleton makes the cross-linked structure more stable, so that the adhesive film has a stronger body strength; on the other hand, the three siloxane bonds are hydrolyzed to produce silanols, which react with the hydroxyl groups on the glass surface to form a chemical bond of silicon oxygen silicon. The chemical bond energy is strong, which can make the adhesive film and the glass form a strong bond, and can remain stable even in a high temperature and high humidity environment, thereby effectively improving the life of the photovoltaic module.

[0010] The cross-linking silane coupling agent can completely replace the tackifier and partially replace the cross-linking agent. Moreover, since the cross-linking silane coupling agent also contains an isocyanate skeleton, the stability of the encapsulation film in a high temperature and high humidity environment is also higher, and the mechanical properties are also improved. However, if the cross-linking silane coupling agent completely replaces the cross-linking agent, the cross-linking efficiency will decrease due to the reduction of active groups for cross-linking.

[0011] Preferably, in formula (I), R1 is a C1-C2 alkyl group.

[0012] Preferably, the base resin is a polyolefin resin. More preferably, the base resin is a vinyl resin. Further preferably, the base resin is one or more of EVA resin (ethylene-vinyl acetate polymer) and POE resin (ethylene-alpha olefin copolymer).

[0013] Preferably, the auxiliary cross-linking agent is at least one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, and trimethylolpropane trimethyl triacrylate.

[0014] Preferably, the raw material of the packaging film further includes a non-cross-linked silane coupling agent, which does not exceed 0.5 parts by mass.

[0015] Preferably, the non-crosslinked silane coupling agent is at least one of vinyltrimethoxysilane, vinyltriethoxysilane, vinyl bond-containing silane oligomer, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane.

[0016] Preferably, the initiator is an organic peroxide initiator. More preferably, the initiator is one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane, bis(3,5,5-trimethylhexanoyl) peroxide, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy-nonanoate, tert-butyl peroxy-2-ethylhexanoate, and tert-butyl peroxy-isopropyl carbonate.

[0017] Preferably, the anti-aging aid includes at least one of an acid-base buffer, an antioxidant, a light stabilizer and an ultraviolet light absorber.

[0018] Preferably, the acid-base buffer is at least one of hydrotalcite, aluminum oxide, magnesium hydroxide, calcium hydroxide, mica flakes, aluminum silicate, calcium silicate, magnesium oxide, zinc oxide, and silicon dioxide.

[0019] Preferably, the antioxidant is at least one of antioxidant 1010, antioxidant 1135, antioxidant 1076, antioxidant 1035, and antioxidant 168.

[0020] Preferably, the light stabilizer is at least one of UV770, UV944, UV292 and UV622.

[0021] Preferably, the ultraviolet light absorber is at least one of UV531, UV328, UV329, UV400, UV1164, and UV3030.

[0022] In a second aspect, the present invention also provides a method for preparing a packaging film for solar modules, comprising the following steps: uniformly mixing the components of the raw materials, sequentially extruding the components into films, and cooling and shaping the components to obtain the packaging film.

[0023] Preferably, the preparation of the cross-linking silane coupling agent comprises: mixing hydroalkoxysilane, triallyl isocyanurate (TAIC) and an organic solvent, heating and refluxing at 50-60° C. in an inert gas atmosphere for 2-4 hours in the presence of a catalyst and a carboxylic acid to obtain a cross-linking silane coupling agent.

[0024] Preferably, the hydrogen alkoxysilane is at least one of trimethoxy hydrogen silane and triethoxy hydrogen silane.

[0025] Preferably, the organic solvent is toluene; the catalyst is a metal platinum catalyst; and the carboxylic acid is acetic acid.

[0026] Preferably, the ratio of the added amounts of the hydroalkoxysilane, the platinum catalyst, toluene, acetic acid and TAIC is 25-35 g: 0.1-0.3 mL: 40-60 g: 0.4-1.0 mL: 50 g.

[0027] Compared with the prior art, the present invention has the following beneficial effects: by adopting a cross-linking-assisting silane coupling agent, a cross-linking reaction occurs with the matrix resin and chemical bonding occurs with the glass interface, thereby completely replacing the tackifier and partially replacing the cross-linking-assisting agent; the cross-linking-assisting silane coupling agent and the cross-linking-assisting agent component cooperate with each other, and during the use of the adhesive film and the lamination of the components, the strength of the adhesive film itself is increased while the bonding strength with the glass is greatly improved; the stability in a high temperature and high humidity environment is also higher, ensuring that there is no delamination during long-term aging, thereby extending the life of the packaging adhesive film. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto.

[0029] Example 1

[0030] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of cross-linking agent (triallyl isocyanurate), 0.6 parts of cross-linking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0031] The cross-linking silane coupling agent is prepared by the following steps: 25 g trimethoxyhydrosilane, 0.1 mL Pt catalyst (metal platinum, activated carbon as carrier), 40 g toluene, 0.40 mL acetic acid, and 50 g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a 55° C. oil bath in a nitrogen atmosphere for 2.5 h, and then the product is distilled at 100° C. and 0.1 mPa low pressure to obtain a cross-linking silane coupling agent having a structure shown in the following formula (I):

[0032] (I); In formula (I), R1 is methyl.

[0033] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0034] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0035] Example 2

[0036] The difference from Example 1 is that 1 part of cross-linking silane coupling agent is used.

[0037] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of cross-linking agent (triallyl isocyanurate), 1 part of cross-linking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0038] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0039] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0040] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0041] Example 3

[0042] The difference from Example 1 is that 0.1 part of non-crosslinking silane coupling agent is used to replace 0.1 part of auxiliary crosslinking silane coupling agent.

[0043] The raw materials of the encapsulation film for solar panels include the following components in parts by mass: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of co-crosslinking agent (triallyl isocyanurate), 0.5 parts of co-crosslinking silane coupling agent, 0.1 parts of non-crosslinking silane coupling agent (γ-methacryloxypropyltrimethoxysilane), 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0044] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0045] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0046] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0047] Example 4

[0048] The difference from Example 1 is that a cross-linking silane coupling agent with a different structure is used.

[0049] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of cross-linking agent (triallyl isocyanurate), 0.6 parts of cross-linking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0050] The cross-linking silane coupling agent is prepared by the following steps: 25 g triethoxyhydrosilane, 0.1 mL Pt catalyst (metal platinum, activated carbon as carrier), 40 g toluene, 0.40 mL acetic acid, and 50 g tripropylene isocyanurate (TAIC) are mixed evenly, and then heated to reflux in a nitrogen atmosphere at 55° C. in an oil bath for 2.5 h, and then the product is distilled at 100° C. and 0.1 mPa low pressure to obtain a cross-linking silane coupling agent having a structure shown in the following formula (I):

[0051] (I); In formula (I), R1 is ethyl.

[0052] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0053] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0054] Example 5

[0055] The difference from Example 1 is that a different resin system is used.

[0056] Calculated by weight, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of POE resin, 0.8 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.4 parts of co-crosslinking agent (triallyl isocyanurate), 0.6 parts of co-crosslinking silane coupling agent, 0.1 parts of antioxidant (antioxidant 1074), and 0.1 parts of light stabilizer (UV292).

[0057] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0058] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0059] The raw material components were mixed according to the proportion and mixed at high speed for 12 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer POE film with a gram weight of 360g / cm 2 .

[0060] Example 6

[0061] The difference from Example 5 is that 0.1 part of the non-crosslinking silane coupling agent is used to replace 0.1 part of the auxiliary crosslinking silane coupling agent.

[0062] The raw materials of the encapsulation film for solar panels include the following components in parts by mass: 100 parts of POE resin, 0.8 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.4 parts of co-crosslinking agent (triallyl isocyanurate), 0.5 parts of co-crosslinking silane coupling agent, 0.1 parts of non-crosslinking silane coupling agent (γ-methacryloxypropyltrimethoxysilane), 0.1 parts of antioxidant (antioxidant 1074), and 0.1 parts of light stabilizer (UV292).

[0063] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0064] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0065] The raw material components were mixed according to the proportion and mixed at high speed for 12 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer POE film with a gram weight of 360g / cm 2 .

[0066] Comparative Example 1

[0067] The difference from Example 1 is that 0.3 parts of a co-crosslinking agent (triallyl isocyanurate) and 0.6 parts of a non-crosslinking silane coupling agent (γ-methacryloxypropyltrimethoxysilane) are used, and no co-crosslinking silane coupling agent is added.

[0068] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of co-crosslinking agent (triallyl isocyanurate), 0.6 parts of non-crosslinking silane coupling agent (γ-methacryloxypropyltrimethoxysilane), 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0069] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0070] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0071] Comparative Example 2

[0072] The difference from Example 1 is that 0.6 parts of a co-crosslinking agent (triallyl isocyanurate) and 0.3 parts of a non-crosslinking silane coupling agent (γ-methacryloxypropyltrimethoxysilane) are used, and no co-crosslinking silane coupling agent is added.

[0073] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.6 parts of co-crosslinking agent (triallyl isocyanurate), 0.3 parts of non-crosslinking silane coupling agent (γ-methacryloxypropyltrimethoxysilane), 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0074] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0075] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0076] Comparative Example 3

[0077] The difference from Example 1 is that 0.9 parts of auxiliary cross-linking silane coupling agent is used, and no auxiliary cross-linking agent and non-cross-linking silane coupling agent are added.

[0078] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.9 parts of cross-linking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0079] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0080] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0081] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0082] Comparative Example 4

[0083] The difference from Example 1 is that 0.1 part of cross-linking silane coupling agent is used.

[0084] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of co-crosslinking agent (triallyl isocyanurate), 0.1 parts of co-crosslinking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0085] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0086] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0087] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0088] Comparative Example 5

[0089] The difference from Example 1 is that the amount of the cross-linking silane coupling agent added is too much (1.3 parts).

[0090] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of cross-linking agent (triallyl isocyanurate), 1.3 parts of cross-linking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0091] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0092] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0093] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0094] Comparative Example 6

[0095] The difference from Example 1 is that the weight fractions of the auxiliary cross-linking agent and the auxiliary cross-linking silane coupling agent used are different.

[0096] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.6 parts of co-crosslinking agent (triallyl isocyanurate), 0.3 parts of co-crosslinking silane coupling agent, 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0097] Among them, the cross-linking silane coupling agent is prepared by the following steps: 25g trimethoxyhydrosilane, 0.1mL Pt catalyst (metal platinum, activated carbon as carrier), 40g toluene, 0.40.mL acetic acid, 50g tripropylene isocyanurate (TAIC) are mixed evenly, heated to reflux in a nitrogen atmosphere in an oil bath at 55°C for 2.5h, and then the product is distilled at 100°C and 0.1mPa low pressure to obtain a cross-linking silane coupling agent having a structure as shown in formula (I) in Example 1.

[0098] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0099] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0100] Comparative Example 7

[0101] The difference from Example 1 is that a cross-linking silane coupling agent with another structure (diallyltetramethyldisiloxane, CAS No.: 17955-81-6) is used, which contains two allyl groups and two siloxane bonds.

[0102] Calculated by mass, the raw materials of the encapsulation film for solar panels include the following components: 100 parts of EVA resin, 0.7 parts of initiator (tert-butyl peroxyisopropyl carbonate), 0.3 parts of co-crosslinking agent (triallyl isocyanurate), 0.6 parts of co-crosslinking silane coupling agent (diallyltetramethyldisiloxane), 0.1 parts of acid-base buffer (aluminum oxide), 0.1 parts of antioxidant (antioxidant 1010), and 0.1 parts of light stabilizer (UV770).

[0103] The above-mentioned encapsulation film for solar panels is prepared by the following steps:

[0104] The raw material components were mixed according to the proportion and mixed at high speed for 6 hours. After the additives were completely absorbed, the process temperature was 100℃ and the cast extrusion was carried out to obtain a single-layer EVA film with a gram weight of 400g / cm 2 .

[0105] The encapsulating film was prepared according to the method in Examples 1-8 and Comparative Examples 1-5, and the crosslinking degree of the encapsulating film and the peel strength between the encapsulating film and the glass were tested at the initial stage before aging and after PCT 48 h (PCT conditions were set as follows: temperature 121° C., pressure 0.2 MPa, humidity 100%). The results are shown in Table 1.

[0106] Table 1 Test results of the bonding performance of the encapsulation film

[0107]

[0108] As shown in Table 1, the present invention adopts a cross-linking silane coupling agent, which cooperates with the cross-linking agent component to improve the bonding strength with the glass, and at the same time, the stability in a high temperature and high humidity environment is also higher, ensuring that there is no delamination during long-term aging and extending the life of the packaging film.

[0109] Example 1 and Comparative Examples 1-3 show that the cross-linking silane coupling agent can completely replace the non-cross-linking silane coupling agent, and due to the particularity of the structure of the cross-linking silane coupling agent, the encapsulation film can have better bonding performance and aging resistance. However, the cross-linking silane coupling agent cannot completely replace the cross-linking agent. When only the cross-linking silane coupling agent is used in Comparative Example 3, the encapsulation film can maintain good bonding performance, but due to the reduction in cross-linking speed, the cross-linking degree of the film will be reduced, and the aging resistance will be reduced. Moreover, the mass fraction of the cross-linking silane coupling agent replacing the cross-linking agent also needs to be limited. In Comparative Example 4, the amount of cross-linking silane coupling agent added is too little, which is not conducive to the encapsulation film obtaining good bonding performance. In Comparative Example 5, the amount of cross-linking silane coupling agent added is too much, and the wetting performance of the film and glass deteriorates while the cross-linking degree is greatly improved. Instead, it is easier to enter water vapor during PCT aging and destroy the interfacial bonding, and the aging resistance of the film deteriorates.

[0110] Example 1 and Comparative Example 6 show that under the conditions of the raw material formula of the present invention, the addition ratio of the cross-linking silane coupling agent and the cross-linking agent also needs to be limited. If the amount of the cross-linking silane coupling agent added is too small, the bonding performance of the encapsulation film will be reduced, and it will not be conducive to obtaining better aging resistance.

[0111] Examples 1, 4 and Comparative Example 7 show that the cross-linking silane coupling agent of the present invention has a specific structure, and under the conditions of the component ratio of the synergistic cross-linking agent, it can play a better effect in the film formulation system of the present invention, while the encapsulation film prepared by the cross-linking silane coupling agent in Comparative Example 7 has poor bonding performance and aging resistance.

[0112] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A packaging film for solar panels, characterized in that: The raw materials are the following components by mass: 100 parts of base resin, 0.1-1 parts of initiator, 0.5-1 parts of cross-linking auxiliary silane coupling agent, 0.1-0.5 parts of cross-linking auxiliary agent, 0.1-1 parts of anti-aging auxiliary agent and no more than 0.5 parts of non-cross-linking silane coupling agent; the base resin is one or more of EVA resin and POE resin; the cross-linking auxiliary agent is at least one of cyanate ester and acrylate containing three or more carbon-carbon double bonds; the cross-linking auxiliary silane coupling agent has a structure shown in the following formula (I): (I); In formula (I), R1 is a C1-C5 alkyl group; The non-crosslinking silane coupling agent is at least one of vinyltrimethoxysilane, vinyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-(acryloxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(2,3-epoxypropoxy)propyltriethoxysilane, 3-isocyanatepropyltrimethoxysilane and 3-isocyanatepropyltriethoxysilane.

2. The encapsulation film for solar modules according to claim 1, characterized in that: In formula (I), R1 is a C1-C2 alkyl group.

3. The encapsulation film for solar modules according to claim 1, characterized in that: The auxiliary crosslinking agent is at least one of triallyl isocyanurate, triallyl cyanurate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate and trimethylolpropane trimethyl triacrylate.

4. The encapsulation film for solar modules according to any one of claims 1 to 3, characterized in that: The initiator is an organic peroxide initiator.

5. The encapsulation film for solar modules according to claim 4, characterized in that: The initiator is one or more of tert-butyl peroxy-2-ethylhexyl carbonate, tert-amyl peroxy-2-ethylhexyl carbonate, 1,1-di-tert-butyl peroxy-3,3,5-trimethylcyclohexane, bis(3,5,5-trimethylhexanoyl) peroxide, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxy-isononanoate, tert-butyl peroxy-2-ethylhexanoate and tert-butyl peroxy-isopropyl carbonate.

6. The encapsulation film for solar modules according to any one of claims 1 to 3, characterized in that: The anti-aging aid comprises at least one of an acid-base buffer, an antioxidant and a light stabilizer.

7. A method for preparing a packaging film for a solar module according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing various components of the raw materials, sequentially extruding to form a film, and cooling and shaping to obtain a packaging adhesive film.

8. The method for preparing the encapsulation film for solar modules according to claim 7, characterized in that: The preparation of the cross-linking silane coupling agent comprises: mixing hydroalkoxysilane, triallyl isocyanurate and an organic solvent, heating and refluxing at 50-60° C. in an inert gas atmosphere for 2-4 hours in the presence of a catalyst and a carboxylic acid, and obtaining the cross-linking silane coupling agent.

9. The method for preparing the encapsulation film for solar modules according to claim 8, characterized in that: The hydrogen alkoxysilane is at least one of trimethoxy hydrogen silane and triethoxy hydrogen silane.

Citation Information

Patent Citations

  • An encapsulating film, its preparation method and application

    CN112812695B

  • Composite packaging adhesive film for solar packaging material and preparation method of composite packaging adhesive film

    CN109294455A

  • Pre-irradiated white EVA packaging adhesive film for solar packaging material and preparation method

    CN110616047A